2020
DOI: 10.1007/s10570-020-03054-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of aminated cotton fibers as an unconventional sorbent to remove anionic dyes from aqueous solutions

Abstract: This study aimed to investigate the sorption of anionic dyes (Reactive Black 5, Reactive Yellow 84, Acid Red 18, and Acid Yellow 23) by cotton fibers aminated with epichlorohydrin and ammonia water (ACFs) as well by unmodified cotton fibers (CFs). CFs and ACFs were characterized based on FTIR, elemental analysis (C/N content) and pH PZC . The effect of solution pH (pH 2-11) and contact time on the removal of dye was studied as well. The kinetic experimental data were fitted to pseudo-first order, pseudo-second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…With regard to PAC, the results showed that it is similar to unmodified cellulose, as the results showed the presence of the OH stretching with an increase in the bandwidth, which designates the presence of the -N-H. In addition, a weak band was observed with very small intensity at 1301 cm −1 , which designates the occurrence of expansion vibrations of the C-N bond, confirming the presence of an amino substitute in cellulose [50]. Moreover, Figure 1 shows FTIR spectra PAC/MONPs, and the obtained spec-tra revealed that the band that concerned OH converts to low intensity in PAC/NiONPs and disappeared in PAC/CuONPs and PAC/Fe 3 O 4 NPs.…”
Section: Surface Topology Investigationsmentioning
confidence: 70%
See 1 more Smart Citation
“…With regard to PAC, the results showed that it is similar to unmodified cellulose, as the results showed the presence of the OH stretching with an increase in the bandwidth, which designates the presence of the -N-H. In addition, a weak band was observed with very small intensity at 1301 cm −1 , which designates the occurrence of expansion vibrations of the C-N bond, confirming the presence of an amino substitute in cellulose [50]. Moreover, Figure 1 shows FTIR spectra PAC/MONPs, and the obtained spec-tra revealed that the band that concerned OH converts to low intensity in PAC/NiONPs and disappeared in PAC/CuONPs and PAC/Fe 3 O 4 NPs.…”
Section: Surface Topology Investigationsmentioning
confidence: 70%
“…In addition, a weak band was observed with very small intensity at 1301 cm −1 , which designates the occurrence of expansion vibrations of the C-N bond, confirming the presence of an amino substitute in cellulose. [50]. Moreover, Figure 1 shows FTIR spectra PAC/MONPs, and the obtained spectra revealed that the band that concerned OH converts to low intensity in PAC/NiONPs and disappeared in PAC/CuONPs and PAC/Fe3O4NPs.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, a weak peak appeared with very low intensity at 1300 and 1630 cm −1 that indicates the stretching vibrations of the C–N bond and N–H bending vibration, respectively. This is evidence for the presence of the amine substituent on cellulose [ 32 ]. After the precipitation of nMO into Acell, there is a difference in the FTIR spectra of the Acell, as shown in Figure 1 C–E.…”
Section: Resultsmentioning
confidence: 97%
“…Several methods for purifying the reactive dyes colored effluent such as oxidation (Balcioglu et al 2001;El-Desoky et al 2010), coagulation (Vilaseca et al 2014), degradation (Yi et al 2020), photocatalysis (Fan et al 2019), ultrafiltration (Alventosa-de Lara 2012; Aouni et al 2012), adsorption (Janaki et al 2013;Jóźwiak et al 2020), electrocoagulation/adsorption (Bellebia et al 2009), photo-electrochemical treatment (Sala et al 2014), and nanofiltration (Sahraei et el. 2018) have been reported.…”
Section: Introductionmentioning
confidence: 99%